Inclusion as a strategy of author’s discourse (by the material of the book of M. K. Parhots «Autilius: fairy tales for children and adults») - Kamlyuk-Yaroshenko, Lyudmila V. (Journal of the Belarusian State University. Philology, 2023)
The study is devoted to the strategies of the author’s discourse of the book by the Belarusian writer M. K. Parhots «Autilius: fairy tales for children and adults». The article raises the question of inclusion as a factor of artistry. Narrative mechanisms are considered that contribute to overcoming the conﬂict of oppositions own – alien, I – Other, norm – anomaly, ways to replenish the allegedly inferior world of the Other, ways of building an understanding and accepting outlook of the narrator and involving the reader in it. It is stated that the book of fairy tales by M. K. Parhots can be called inclusive not only because it deals with heroes that have special features, but also because inclusiveness becomes the main strategy of narration. In the course of the narrative, contradictions associated with epistemic (knowledge – ignorance), temporal (then – now), spatial (here – there) modality, as well as modality of norms (allowed – forbidden) and modality of assessments (positive – negative) are removed. Special rhetoric allows the author to educate gently the reader so that, identifying himself with the narrator and being in the position of an understanding and accepting addressee, he understand and accepts the Other (alien, strange) as himself.